PERAN MEDIA MASSA DALAM MENINGKATKAN KUALITAS KEPEMERINTAHAN LOKAL BERBASIS HUMAN SECURITY DI KOTA JAYAPURA - Aria Aditya Setiawan, Aria Aditya Setiawan (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
Abstract Mass media constitute the backbone of a good governance especially in a local governance. The media supply the amount of political information that voters base their decisions on. They identify problems in our society and serve as a medium for deliberation. They also play as a watchdogs that we can rely on for uncovering errors and wrongdoings by those in power. The mass media always be a part of people’s life to protect their basic rights.This paper offers two aspects to be reconsidered, first, it will explain the role of mass media in local governance, and the second one, will explain the effect of mass media toward human security in Papua. Keywords : mass media, local governance, human security